ERYTHEMA ELEVATUM DIUTINUM AS MOST PROBABLE DIAGNOSIS: A CASE REPORT - Erick Francisco Sanchez Jimenez (Our Dermatology Online, 2013)
Cutaneous vasculitis can be cause by multiple disorders or can be idiopathic. Many diseases can present with similar findings, therefore histopathologic examination is always require for confirming the right diagnosis. The erythema elevatum diutinum (EED) is a localized vasculitis, classified as a neutrophilic dermatosis. It's a rare cutaneous condition, distribute on the extensor surface of the extremities, more frequently in the dorsum of the hands, knees and elbows. They have a symmetric distribution and can be asymptomatic, painful; or pruritic, sometimes accompanied paresthesias. The most common clinical presentation is round erythematous papules which become erythemato-violaceous or purpuric plaques. There are not pathognomonic histopathological findings, but can present as a leukocytoclastic vasculitis with perivascular neutrophilic infiltration in the middle and superficial dermis. I presented the case of a 61-year-old female, with erythematous purpuric painful plaques, irregular, symmetric and elevated, located in both thenar regions of her hands and paresthesias. The patient's presentation is consistent with multiple characteristics of EED such as the description of the lesions, the anatomical location, the symmetric distribution and the histopathological findings of an initial disease. This patient does not have all the clinical progression and outcome, due to the initial stage of the disease.